1993
DOI: 10.1002/dc.2840090619
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology of the male breast in a cancer center

Abstract: All fine-needle aspirates (FNA) performed on the male breast at The University of Texas M. D. Anderson Cancer Center from 1985 to 1992 were reviewed, totaling 64. The patients' ages ranged from 19 to 86 years, with a mean of 56 years. Thirty-three patients had a history of an extramammary malignancy. The diagnoses established by FNA were gynecomastia (45), mammary carcinomas (6), neoplasms metastatic to the breast (5), suspicious for carcinoma (1), intra-mammary lymph node (1), and lipoma (1). In five cases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 11 publications
3
32
2
Order By: Relevance
“…Core needle biopsy has emerged as a challenger to FNA biopsy in recent decades, especially in high-resource settings. Previous studies have demonstrated high diagnostic accuracy, sensitivity, and specificity of FNA biopsy for breast lesions in both men and women [7, 9, 16, 18, 19, 31, 32]. Our group has shown that FNA biopsy for palpable breast lesions is a rapid, cost-effective, time-efficient method and lacks virtually any contraindication, while maintaining a high specificity and sensitivity and a low nondiagnostic rate [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Core needle biopsy has emerged as a challenger to FNA biopsy in recent decades, especially in high-resource settings. Previous studies have demonstrated high diagnostic accuracy, sensitivity, and specificity of FNA biopsy for breast lesions in both men and women [7, 9, 16, 18, 19, 31, 32]. Our group has shown that FNA biopsy for palpable breast lesions is a rapid, cost-effective, time-efficient method and lacks virtually any contraindication, while maintaining a high specificity and sensitivity and a low nondiagnostic rate [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…10 Sneige et al reported apocrine metaplasia in 5.6% and foamy histiocytes in 22% of cytologic smears obtained from 45 patients with gynecomastia. 8 In our series of 100 patients with gynecomastia, apocrine metaplasia and foamy histiocytes were noted in 8% and 12% of the cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the control group, the cytologic findings in the cases of intraductal carcinoma included numerous crine metaplasia in gynecomastia, 8 while others have specifically stated that apocrine metaplasia and foamy histiocytes are not features of it. 3 Another paper claims that apocrine metaplasia does occur in gynecomastia and that its presence confirms the nonneoplastic nature of the lesion.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, surgical intervention and percutaneous biopsy in men with a palpable breast mass had been performed without breast imaging (3). However, it has been reported that percutaneous biopsies can lead to misdiagnosis (13). As stated Munn et al (14) combined use of mammosonography could substantially reduce the need for biopsy.…”
Section: Discussionmentioning
confidence: 99%